A Reflection on Carl Mannheim’s Theory of Cultural Democracy in The Democratization of Culture - Abdolreza Navah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Karl Mannheim is a Hungarian-German sociologist and one of the leading figures in the sociology of knowledge during thirty decades of the twentieth century thirty centuries and at the same time with the rise of the National Socialist Party. He sees democracy not only as a political phenomenon but also as a prelude to the spread of democratic culture, as well as a consequence of a kind of social turmoil resulting from the displacement of classes and civic values replacing the traditional values of the bourgeois aristocracy. In this work, Mannheim tries to describe the process of transformation in sociological but abstract language. In general, it can be said that Mannheim, by focusing on the discussion of culture, has tried to show what factors hinder the realization of democracy in societies in transition and finally has offered solutions in this regard.